The Immunogenicity of Plant-produced Human Papillomavirus (HPV) Virus-like particles (VLPs) in Mice - Naupu, Paulina Ndinelago (Department of Molecular and Cell Biology, 2020)
Cervical cancer is caused by infection with high-risk Human papillomaviruses (HPVs). It is ranked fourth among the top cancers in women worldwide, with ~87% of the global cervical cancer cases reported in developing countries. The HPV L1 capsid protein can self-assemble into virus-like particles (VLPs) that are structurally like native virions, which is the foundation on which commercially available vaccines have been developed. There are 3 commercially available HPV vaccines that are effective at preventing HPV infections, but are expensive, therefore limiting their use in the poorer developing countries where they are most needed. Thus, there is a need for more cost-effective HPV vaccines for use in these countries. Over the years, the use of plants to produce vaccines has begun to be more favourably looked upon as a costeffective alternative to conventionally used expression systems. The aim of this study was to evaluate the plant-based transient expression system as a tool to produce potentially cost-effective HPV L1 VLP-based vaccines, particularly for developing countries. Firstly, the L1 proteins of the 8 most common high-risk Human papillomavirus types in Africa (HPV 16, 18, 31, 33, 35, 45, 52, and 58) and 2 low risk types (HPV 6 and 34) were transiently expressed in Nicotiana benthamiana. The proteins were purified via isopycnic ultracentrifugation using sucrose and Optiprep™ density gradients, and the assembly of VLPs assessed by transmission electron microscopy (TEM). To further assess whether the VLPs are immunogenic, HPV 35, 52 and 58 were selected for mice studies. These were selected in particular, as HPV 35 is the fifth most prevalent type in Africa, and HPV 52 and 58 are among the most frequently reported high-risk types in Sub-Saharan Africa. VLPs representing the 3 HPV types were quantified and prepared for immunization in mice. The commercially available Gardasil® HPV VLP vaccine was used as a positive control. The immunogenicity of the vaccines was evaluated by testing for the presence of anti-L1 antibodies in sera from immunized mice using enzyme-linked immunosorbent assays (ELISAs) and western blots. Sera from immunized mice were also tested for the presence of neutralizing antibodies using pseudovirion based neutralization assays (PBNAs). L1 proteins of all 10 HPV types tested were successfully expressed in N. bethamiana, and TEM analysis showed that expression resulted in the successful formation of fully assembled VLPs (40-60nm) as well as small VLPs and/or capsomeres (25-39nm). The analysis of the immune response showed that type-specific L1-specific antibodies were produced which were able to successfully neutralize homologous pseudovirions (PsVs) in PBNAs. Sera from mice immunized with plant-produced VLPs were further tested against heterologous HPV 6, 16, 18, 31, and 45 PsVs. However, none of the tested heterologous HPVs were neutralized, suggesting that plant-made VLPs induced type-specific neutralizing antibodies only. In conclusion, this study successfully demonstrated the potential for using plant-based transient expression systems to produce affordable and immunogenic HPV vaccines, particularly for developing countries. This is the first study describing the expression of 10 HPV L1 proteins in plants, marking a step towards the development of cheaper HPV vaccines which could be combined to generate an effective multivalent vaccine against HPVs.